P01.135 User experience with new, aesthetically improved transducer arrays for delivery of tumor treating fields for glioblastoma. (19th September 2018) - Kinzel, A; Graeb, M; Grewal, J; Kirson, E
Abstract: Background: Tumor Treating Fields (TTFields) are low-intensity, intermediate frequency alternating electric fields for glioblastoma treatment. TTFields are administered using the Optune® system, comprised of two main components - an electric field generator and insulated transducer arrays (TAs). The current TAs consist of 2 opposing pairs of TAs having ceramic disks arranged within a white adhesive bandage, designed to hold the TAs tightly to the shaved scalp. In response to patient and healthcare provider requests, Novocure TM evaluated tan colored TAs to minimize the stark appearance of white TAs for patients, making the TAs more amenable for use in public settings. Material and Methods: This study was carried out in 25 newly diagnosed and recurrent GBM patients in Germany receiving Optune. Patients with KPS ≥70, caregiver support and skin intact at study initiation were asked to complete a questionnaire, which assessed patient satisfaction with the comfort, aesthetics and convenience associated with the tan TAs. Results: Patients reported responses to questionnaire at day 0 (white arrays), days 7 and 28 (wearing the tan arrays). Median patient reported changes from baseline to Day 28 in responses in the questionnaire were compared using a Wilcoxon signed rank test. Results: Patients reported the color of TAs to be an important attribute ( p<0.011 ). The tan arrays were less conspicuous than white arrays ( p<0.0052). Participants in Germany found tan color was neither too dark nor too light ( p<0.001 ). Participants felt that wearing the tan arrays were significantly cooler than the white arrays. Conclusion: Optune is designed to be integrated into patients' daily life. Results from phase 3 clinical trials showed a correlation between efficacy of TTFields and daily treatment duration. Therefore, improvements addressing patients' user experience with the tan colored TAs, which minimize calling attention to the patients' medical condition, may help to further improve treatment compliance and patient satisfaction.